Guru Wali dalam Perspektif Bimbingan Konseling (Peran guru wali sebagai beban tambahan bagi guru umum di sekolah) - Saputra, Teuku Amnar; Zuriah (Department of Islamic Guidance and Counseling, 2025)
This study aims to analyze the role of school counselors from the perspective of the Guidance and Counseling discipline. The study was conducted using library research with a qualitative descriptive approach, analyzing various academic literature and the latest educational regulations, including Permendikdasmen Number 11 of 2025. The results indicate that counseling services are professional activities that can only be performed by school counselors or school counselors with a minimum academic qualification of a Bachelor's degree (S-1) in Guidance and Counseling and possess pedagogical, social, personality, and professional competencies as stipulated in Permendikdasmen Number 27 of 2008. Meanwhile, school counselors serve as collaborative partners with school counselors, not as counselors. Permendikdasmen Number 11 of 2025 stipulates that school counselors have the function of providing academic and character support to students and are required to collaborate with school counselors in addressing student issues. School counselors play a role in implementing preventive guidance and monitoring student development, but do not have the professional authority to conduct therapeutic counseling. The conceptual and functional distinction between guidance and counseling is crucial for maintaining clarity of scope and professionalism in the school environment.